Alteration of Hormone Levels in Transgenic Tobacco Plants Overexpressing the Rice Homeobox Gene OSH1 - Kusaba, Shinnosuke (American Society of Plant Physiologists, 1998)
The rice (Oryza sativa L.) homeobox gene OSH1 causes morphological alterations when ectopically expressed in transgenic rice, Arabidopsis thaliana, and tobacco (Nicotiana tabacum L.) and is therefore believed to function as a morphological regulator gene. To determine the relationship between OSH1 expression and morphological alterations, we analyzed the changes in hormone levels in transgenic tobacco plants exhibiting abnormal morphology. Levels of the plant hormones indole-3-acetic acid, abscisic acid, gibberellin (GA), and cytokinin (zeatin and trans-zeatin [Z]) were measured in leaves of OSH1-transformed and wild-type tobacco. Altered plant morphology was found to correlate with changes in hormone levels. The more severe the alteration in phenotype of transgenic tobacco, the greater were the changes in endogenous hormone levels. Overall, GA(1) and GA(4) levels decreased and abscisic acid levels increased compared with wild-type plants. Moreover, in the transformants, Z (active form of cytokinin) levels were higher and the ratio of Z to Z riboside (inactive form) also increased. When GA(3) was supplied to the shoot apex of transformants, internode extension was restored and normal leaf morphology was also partially restored. However, such GA(3)-treated plants still exhibited some morphological abnormalities compared with wild-type plants. Based on these data, we propose the hypothesis that OSH1 affects plant hormone metabolism either directly or indirectly and thereby causes changes in plant development.